2019
DOI: 10.1126/science.aau8861
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing meiotic recombination revealed by whole-genome sequencing of single sperm

Abstract: Recombination is critical to meiosis and evolution, yet many aspects of the physical exchange of DNA via crossovers remain poorly understood. We report an approach for single-cell whole-genome DNA sequencing and sequence 217 individual hybrid mouse sperm, providing a kilobase-resolution genome-wide map of crossovers. Combining this map with molecular assays measuring stages of recombination, we identify factors that affect crossover probability, including PRDM9 binding on the non-initiating template homologue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
184
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(222 citation statements)
references
References 69 publications
14
184
2
Order By: Relevance
“…driven by expected WT ZCWPW1 recruitment levels at each hotspot (Supplementary Figure 15). ZCWPW1 therefore offers a (thus far) unique protein, linking PRDM9 binding with its downstream functions (Davies et al, 2016;Hinch et al, 2019;R. Li et al, 2019) in aiding rapid DSB processing/repair at hotspots whose homologue is bound by PRDM9.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…driven by expected WT ZCWPW1 recruitment levels at each hotspot (Supplementary Figure 15). ZCWPW1 therefore offers a (thus far) unique protein, linking PRDM9 binding with its downstream functions (Davies et al, 2016;Hinch et al, 2019;R. Li et al, 2019) in aiding rapid DSB processing/repair at hotspots whose homologue is bound by PRDM9.…”
Section: Discussionmentioning
confidence: 99%
“…This is thought to reflect a wider phenomenon of faster DSB repair occurring within those hotspots whose homologue is more strongly bound by PRDM9, i.e. those hotspots with a stronger H3K4me3 signal in the WT mouse (Davies et al, 2016;Hinch et al, 2019;R. Li et al, 2019).…”
Section: Dmc1 Persistencementioning
confidence: 99%
See 1 more Smart Citation
“…The ability to target DSBs to open chromatin is critical for meiotic recombination. In mice, meiotic DSBs(Baker et al, 2014;Lange et al, 2016) and crossovers identified through single-sperm sequencing(Hinch et al, 2019) are concentrated within hotspot NDRs. In the absence of open chromatin at hotspots, by loss of either HELLS or PRDM9, SPO11 preferentially targets other regions of accessible chromatin to create DSBs, even when the effect of these ectopic breaks is usually blocked meiotic progress and infertility.…”
mentioning
confidence: 99%
“…The advent of whole genome sequencing has permitted high resolution crossover maps, by identifying regions of the genome where parental haplotypes change in recombinant individuals (Kulathinal et al 2008;Rockman and Kruglyak 2009;Dumont et al 2011;Miller et al 2012;Comeron et al 2012) . More recently, single-cell sequencing technologies have further extended such high-throughput crossover detection directly from sperms (Hinch et al 2019) . While providing impressive resolution often at the level of individual bases, these approaches are difficult to scale, as each recombinant individual/cell requires a separate library preparation and/or barcode.…”
Section: Introductionmentioning
confidence: 99%